2013
DOI: 10.1002/wcms.1125
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory in materials science

Abstract: Materials science is a highly interdisciplinary field. It is devoted to the understanding of the relationship between (a) fundamental physical and chemical properties governing processes at the atomistic scale with (b) typically macroscopic properties required of materials in engineering applications. For many materials, this relationship is not only determined by chemical composition, but strongly governed by microstructure. The latter is a consequence of carefully selected process conditions (e.g., mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 59 publications
1
81
0
2
Order By: Relevance
“…Indeed, simulation of defects in general and doping in particular has recently been pointed out as an ongoing challenge in computational materials science. 11 Because doping does not significantly alter the chemical and crystalline host properties, in many cases pertinent physics can be well captured even in a simulation involving an intrinsic semiconductor. 4,5,8 For example, the space charge region (SCR) that develops at semiconductor surfaces is often on the order of micrometers for moderately doped semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, simulation of defects in general and doping in particular has recently been pointed out as an ongoing challenge in computational materials science. 11 Because doping does not significantly alter the chemical and crystalline host properties, in many cases pertinent physics can be well captured even in a simulation involving an intrinsic semiconductor. 4,5,8 For example, the space charge region (SCR) that develops at semiconductor surfaces is often on the order of micrometers for moderately doped semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches in the field of materials science [50][51][52] have demonstrated that density functional theory (DFT) provides the best means for predicting solid state properties of materials close to experimental observations [53]. In this study, we use DFT based on the all-electron FPÀ LAPWþlo method, as implemented in the WIEN2K package [54], to investigate the structural, electronic and magnetic properties of Vanadium doped BeS and BeTe with concentration (x¼ 0, 0.25, 0.50, 0.75 and 1.0).…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…Potentials produced by the code are directly usable with the LAMMPS [8] or Camelion [9] molecular-dynamics packages.…”
Section: Nature Of Problemmentioning
confidence: 99%
“…In spite of its wide-ranging successes however [9], DFT is limited to relatively small system sizes (typically less than 1000 atoms) and time-scales. This renders the method inappropriate for modelling many atomistic processes, including for example fracture or the dynamics of dislocation interactions, where realism is only achieved when millions of atoms are considered.…”
Section: Introductionmentioning
confidence: 99%